Estudo do método de parâmetros fundamentais em fluorescência de raios X - Silva, George Kummel Soares Figueiredo Castro (2012)
The characterization of materials, both from the standpoint of qualitative and quantitative has been done since the 50's by several researchers using the FRX technique in combination with mathematical methods for correction of matrix effects of absorption and enhancement, among which stood out The method of basic parameters and algorithms influence coefficients. Such methods are crucial in practice for correction of matrix effects occurring within a sample. Both methods have as a base solving equations Sherman, relating the intensities of fluorescent X-rays primary, secondary and tertiary etc. with concentrations of components of samples of known composition. The equations developed by Sherman, 1955, and Fujino and Shiraiwa corrected by the factors 1/2 and 1/4 for the fluorescence intensity of secondary and tertiary, have the drawback of not being invertible algebraically. Thus rendering the analysis of samples of unknown composition being made unfeasible in practice. To solve this problem, several scientists since 1968 have developed algorithms, which in practice can numerically inverting the relationship between mass concentrations or fractions present in a sample of unknown composition with the fluorescent intensities. These algorithms already contains the necessary factors for correction of matrix effects and use iterative methods for calculating approximate concentrations or mass fractions of the actual sample. In this study we analyzed samples SQ1N, SQ2NN, SQ3N and STG2, using the FRX technique in combination with the method of basic parameters for the calculation of the elemental concentrations or weight fractions of the elements present in the sample. In this paper, according to the procedure described in materials and methods section, we determined first the instrumental sensitivity (gi factors) for each element using the intensities measured experimentally. Then making an approximation to the initial concentration, Ci = Ri (where ignored the effects matrix), and also using factors determined gi, was calculated using a computer program made in Delphi 7, a set of nonlinear equations (equations Sherman) correlating the concentrations of each of the various elements present in the sample with the characteristics of the x-ray intensities for iterative processes. At the end of the calculations comparing these various compositions acceptable ranges for the samples mentioned with the same patterns, obtained by Ray Fluorescence spectrometer Dispersion Wavelength instrumental and experimental conditions described in Chapter 3 (section Materials and methods). By analysis of results obtained verified the importance of fundamental parameter method and precision for quantization of any one unknown sample; well as the influence of the basic parameters and experimental conditions instrumental in the quantification of samples.